2018
DOI: 10.3892/ijmm.2018.3595
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PVT1 promotes the angiogenesis of vascular endothelial cell by targeting miR‑26b to activate CTGF/ANGPT2

Abstract: Angiogenesis is essential for various biological processes, including tumor blood supply delivery, cancer cell growth, invasion and metastasis. Plasmacytoma variant translocation 1 (PVT1) long noncoding RNA (lncRNA) has been previously reported to affect angiogenesis of glioma microvascular endothelial cells by regulating microRNA (miR)‑186 expression level. However, the specific underlying molecular mechanism of PVT1 regulation of angiogenesis in vascular endothelial cells remains to be elucidated. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
(29 reference statements)
3
31
0
Order By: Relevance
“…Considering the critical regulatory role of PVT1 in the angiogenesis of ECs (17), the present study further focused on the effects of miR-190a-5p on the proliferation of ECs. miR-190a-5p expression in HUVECs was regulated by cell transfection.…”
Section: Mir-190a-5p Suppresses Cell Proliferation Of Huvecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the critical regulatory role of PVT1 in the angiogenesis of ECs (17), the present study further focused on the effects of miR-190a-5p on the proliferation of ECs. miR-190a-5p expression in HUVECs was regulated by cell transfection.…”
Section: Mir-190a-5p Suppresses Cell Proliferation Of Huvecsmentioning
confidence: 99%
“…Increased expression of lncRNA plasmacytoma variant translocation 1 (PVT1) was found in several heart-related abnormalities, such as cardiac hypertrophy (15) and atrial fibrosis (16). In addition, Zheng et al (17) showed the promotive effects of PVT1 on the angiogenesis of ECs. However, to the best of our knowledge, the role of PVT1 in CHF has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…miR-146a is known to be cardioprotective and to reduce infarct size in in vivo animal models of AMI [48]. miR-186 was shown to play a crucial role in vascular endothelial cell angiogenesis [49]. miR-221 was shown to inhibit autophagy after hypoxia and was postulated to be a possible target in treating ischemia-reperfusion injury [50].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PVT1-binding of miR-186 led to upregulation of the autophagy-promoting genes ATG7 and Beclin1, with increased migration of glioma vascular endothelial cells [123]. Similarly, PVT1 enhanced in vitro vascular tube formation of HUVECs by enforcing the expression of CTGF and ANGPT2, through miR-26b suppression [124]. The pro-angiogenic function of PVT1 is also exerted through direct interaction with phospho-STAT3, leading to protein stabilization and activation of the downstream pathway, resulting in VEGFA upregulation in gastric cancer [125].…”
Section: Pvt1 and Circpvt1: Myc Partners In Crime And Beyondmentioning
confidence: 97%